ISOLASI DAN KARAKTERISASI BAKTERI ENDOFIT DARI BATANG TUMBUHAN KAMBOJA PUTIH (Plumeria acuminata Ait) - Hidayati, Mila Nurul (P3M STIKes Bakti Tunas Husada, 2019)
Endophytic bacteria is a bacteria found in the tissue’s plant that does not provide an infection or a negative effect on its host plant. Endophytic bacteria can be found in various types of plants, especially plants that are often used as medicinal plants. One of them is Kamboja Putih (Plumeria acuminata Ait.) which has secondary metabolite such as alkaloids, flavonoids, tannins, and terpenoids. Endophytic bacteria can produce the same bioactive components as their host plants, so it can potentially be developed in the world of health. The purpose of this research was to determine the presence of endophytic bacteria and characteristic isolated from P.acuminata stem. This is an explorative research, using an isolation method to get endophytic bacteria. P.acuminata stem is sterilized and inoculated on Nutrient Agar, and then it is incubated until the isolate is obtained. To know the characteristic of endophytic bacteria, macroscopic characteristics were observed such as shape, color, edges and surface of colony and microscopic characteristics from endophytic bacteria was observed by Gram stain. Moreover, to know the characteristics of secondary metabolites that exist in endophytic bacteria it has to be done phytochemical screening to the obtained isolate, include test of flavonoids, tannins, triterpenoids, alkaloids and saponins. The results of the research showed that Kamboja has endophytic bacteria, that are endophytic bacterial isolates EI and E2. The characteristics of both endophytic bacterial isolates are round, whitish, intact edges and flat surfaces of the colonies. The types of both bacterial isolates EI and E2 are Gram positive and coccus-shaped bacteria. Phytochemical screening tests show that endophytic bacterial isolates can produce alkaloids both on ordinary fermentation medium and those already given precursors of acetic acid Keywords: Plumeria acuminata Ait, endophytic bacteria, isolation and characterization endophytic bacteria.